ELDERLY SUPPORT APPLICATION “CHEERS” (CASE STUDY: CITY OF DERABIN NORTH MELBOURNE, AUSTRALIA) - Fajri, Hersanto (Fakultas Teknik dan Sains, Universitas Ibn Khaldun Bogor, 2015)
In the society that we are living in, service is one of the most important things that keep an order to a society or a community to function well. This research’s target audiences are the current active elderly and the upcoming future generation elderly among the age of 60 to 80. The area of Darebin, North Melbourne will be the chosen site for this research. Based on some research data, it shows that the rates of the third age are increasing time by time and there are not many options of elderly services out there in our society (BCL, 2010). What researcher found from field observation are the existing services for the elderly often provides negative impressions to the users instead of positive ones. For instance, the lack of freedom is the most common thing that is experienced by most elderly who lives in an elderly centre. It is depressing and the lack of intense care in the retirement village is often being encountered. The other elderly service which is the residential age care facilities is not affordable for everyone although it provides better services to the users. Since Australia consists of multi-cultural people from all around the world, therefore the need of creating helpful services in the field of technology information to assist them to live well is a big achievement for this research.